Serum Metals in Breast Cancer Patients: A comparative study conducted at Hyderabad and its Adjoining Areas, Pakistan - Laghari, Mubina; Aslam Channa, Naseem; Shaikh, Marvi; Hameed, Sarwa; Mumtaz, Nazia; Hameed, Zuha (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To measure the concentrations of various metals in the blood serum of breast cancer patients from Hyderabad and surrounding areas and compare them with healthy controls. METHODOLOGY: This comparative case-control study was conducted at the Institute of Biochemistry, University of Sindh, Jamshoro. Samples were collected from the surgical wards at Liaquat University of Medical & Health Sciences. The study included 518 participants, including 259 newly diagnosed breast cancer patients with a mean age of 51.10±7.761 and no prior radio or chemotherapy treatment. Patients who had previous breast surgery were excluded. The study also included 259 age-matched healthy controls without a history of cancer. After obtaining the participants’ sociodemographic characteristics, blood samples were collected and analyzed for serum metal concentrations using inductively coupled plasma optical emission spectrometry (ICP-OES). Data were analyzed using SPSS version 20.0. p < 0.05 was considered significant at the 95% confidence interval. RESULTS: We found the majority of the breast cancer patients were less than 50 years of Age, illiterate, and belonged to Hyderabad district and Punjabi by ethnicity. The results revealed significant differences in metal concentrations between breast cancer patients and controls, with elevated levels of aluminium, cobalt, chromium, and lead. At the same time, elements like arsenic and zinc were lower in breast cancer patients. CONCLUSION: The findings suggest that the serum metal concentration may be linked to breast cancer pathogenesis, highlighting the need for further research on environmental risk factors in breast cancer progression.